Blindness Above And Below The Poverty Line: Reflections from Sofala, Mozambique - Roba, Assegid; Chagunda, Margarida; Machissa, Tiago (My University, 2020)
Objective: Although the correlation between visual impairment and poverty has been established, economic assessment is not a standard component of blindness surveys. The purpose of this study was to determine the prevalence of avoidable blindness and its association with poverty in Sofala province of Mozambique. Methods: As part of a Rapid Assessment of Avoidable Blindness, 94% of a random sample of 3600 people >50 years responded to questions regarding daily per capita expenditure. The WHO definition of blindness (presenting visual acuity <3/60) was used to determine the visual status of participants, and the World Bank’s threshold of living on <$1.25 International Dollar a day demarcated the poverty line. Results: The prevalence of blindness was 3.2% [95% Confidence Interval (CI): 2.6, 3.8]. People living below the poverty line had a significantly greater odds of being blind [Odds Ratio (OR): 2.6 (CI: 1.6 to 4.5)]. Age above 60 [OR: 7.0 [CI: 4.6 to 10.80] predicted blindness but the association with illiteracy, gender or rural residence was not significant. Conclusions: Blindness disproportionately affects people living below the poverty line. Development initiatives could augment the impact of blindness prevention programs. Measuring poverty should become a standard component of visual impairment surveys.
Keywords: Blindness; Mozambique; Poverty; Poverty Line; RAAB; Sofala; Visual impairment